XANES and Mg isotopic analyses of spinels in Ca‐Al‐rich inclusions: Evidence for formation under oxidizing conditions. (24th October 2013) - Paque, J. M.; Sutton, S. R.; Simon, S. B.; Beckett, J. R.; Burnett, D. S.; Grossman, L.; Yurimoto, H.; Itoh, S.; Connolly, H. C.
Abstract: Ti valence measurements in MgAl2 O4 spinel from calcium‐aluminum‐rich inclusions (CAIs) by X‐ray absorption near‐edge structure (XANES) spectroscopy show that many spinels have predominantly tetravalent Ti, regardless of host phases. The average spinel in Allende type B1 inclusion TS34 has 87% Ti +4 . Most spinels in fluffy type A (FTA) inclusions also have high Ti valence. In contrast, the rims of some spinels in TS34 and spinel grain cores in two Vigarano type B inclusions have larger amounts of trivalent titanium. Spinels from TS34 have approximately equal amounts of divalent and trivalent vanadium. Based on experiments conducted on CAI‐like compositions over a range of redox conditions, both clinopyroxene and spinel should be Ti +3 ‐rich if they equilibrated with CAI liquids under near‐solar oxygen fugacities. In igneous inclusions, the seeming paradox of high‐valence spinels coexisting with low‐valence clinopyroxene can be explained either by transient oxidizing conditions accompanying low‐pressure evaporation or by equilibration of spinel with relict Ti +4 ‐rich phases (e.g., perovskite) prior to or during melting. Ion probe analyses of large spinel grains in TS34 show that they are enriched in heavy Mg, with an average Δ 25 Mg of 4.25 ± 0.028‰, consistent with formation of the spinel from an evaporating liquid. Δ 25 Mg shows small, but significant, variation, both within individual spinels and between spinel and adjacent melilite hosts. The Δ 25 Mg data are most simply explained by the low‐pressure evaporation model, but this model has difficulty explaining the high Ti +4 concentrations in spinel.